2021
DOI: 10.1111/jcap.12344
|View full text |Cite
|
Sign up to set email alerts
|

Parental opioid use disorder: Examining their children's experiences, needs, and road to resilience

Abstract: Problem Over 8 million children in the United States live with a parent with substance use disorder (SUD), inclusive of opioid use disorder (OUD). This is an adverse childhood experience (ACE), that often leads to poor outcomes such as developing SUD or mental illness. Interventions and research have focused more on the parent and not their children. Without emphasis on child's experiences, their needs, and building interventions toward developing resilience, the intergenerational cycle of SUD/OUD will persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…This impact was described in interviews (Collishaw et al, 2016;Kahl & Jungbauer, 2014) and synonymous with lower self-reported symptom load (Collishaw et al, 2016;Watson et al, 2014). This was corroborated by the findings of Palumbo et al (2022) where adolescents described a desire to remain in the homes of their biological parents despite adversity. Many also felt betrayed by social workers or their relatives for relocating them to foster homes.…”
Section: Resilience Resourcesmentioning
confidence: 56%
See 1 more Smart Citation
“…This impact was described in interviews (Collishaw et al, 2016;Kahl & Jungbauer, 2014) and synonymous with lower self-reported symptom load (Collishaw et al, 2016;Watson et al, 2014). This was corroborated by the findings of Palumbo et al (2022) where adolescents described a desire to remain in the homes of their biological parents despite adversity. Many also felt betrayed by social workers or their relatives for relocating them to foster homes.…”
Section: Resilience Resourcesmentioning
confidence: 56%
“…The adolescents in the study by Palumbo et al (2022) had varying experiences of their substance-using parent, but most described their parent as someone who managed to take care of their basic needs despite active drug misuse. 2016) also declared the importance of the ill or diagnosed parent's ability to express emotions as associated with good mental health in the children growing up with parental mental illness.…”
Section: Family Resourcesmentioning
confidence: 99%
“…These children likely witness their parents in active use, in withdrawal, seeking the drugs, and perhaps in periods of recovery. The environment can be unstable, chaotic, and caregiving for siblings, as well as parentification tends to occur (Palumbo et al, 2021). Given the chronicity of OUD, multiple separations often ensue while that parent is actively using or is in an inpatient drug treatment (Feder et al, 2019).…”
Section: Fostering Better Outcomes For Youth Of Parents With Opioid U...mentioning
confidence: 99%
“…Still, not all families in which a parent has OUD have the same level of dysfunction and some may be able to remain intact with added resources and support (Matjasko et al, 2022). Children often desire to remain with their parents (Palumbo et al, 2021) and some evidence supports that retaining custody facilitates parent's recovery (Hall et al, 2016). The intent of the Family First Prevention Services Act passed in 2018 was to provide families with necessary SUD and behavioral health treatment and to avoid the removal of children (Children's Defense Fund, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation